Os campos magnéticos entre o sonho e a realidade: origens da viagem surrealista de André Breton (1896-1966) - Cavaloti, Thiago Masano (2008)
The objective of the following essay is to analyze the notion of magnetic fields between dream and reality, portrayed in the Surealism Manifesto of 1924 by Andre Breton (1896-1966), throughout inquiries on the theory of the unconscious of Sigmung Freud and the French modern poetic experience present in Charles Baudelaire (1821-1867), Arthur Rimbaud (1854-1891) e Paul Valéry (1871-1945). This careful reading of the propositions of André Breton s Manifesto lies upon the concept of surreality , restoring the author´s poetic-aesthetic notions in light of the experience of the First World War (1914-1918)